Ecteinascidin 743 Interferes with the Activity of EWS-FLI1 in Ewing Sarcoma Cells - Grohar, Patrick J (Neoplasia Press Inc., 2011)
ET-743 (trabectedin; Yondelis) is approved in Europe for the treatment of soft tissue sarcomas. Emerging phase 1 and 2 clinical data have shown high response rates in myxoid liposarcoma in part owing to the inhibition of the FUS-CHOP transcription factor. In this report, we show that modulation of specific oncogenic transcription factors by ET-743 may extend to other tumor types. We demonstrate that, among a panel of pediatric sarcomas, Ewing sarcoma family of tumors (ESFTs) cell lines bearing the EWS-FLI1 transcription factor are the most sensitive to treatment with ET-743 compared with osteosarcoma, rhabdomyosarcoma, and synovial sarcoma. We show that ET-743 reverses a gene signature of induced downstream targets of EWS-FLI1 in two different ESFT cell lines (P = .001). In addition, ET-743 directly suppresses the promoter activity of a known EWS-FLI1 downstream target NR0B1 luciferase reporter construct without changing the activity of a constitutively active control in ESFT cells. Furthermore, the effect is specific to EWS-FLI1, as forced expression of EWS-FLI1 in a cell type that normally lacks this fusion protein, HT1080 cells, induces the same NR0B1 promoter, but this activation is completely blocked by ET-743 treatment. Finally, we used gene set enrichment analysis to confirm that other mechanisms of ET-743 are active in ESFT cells. These results suggest a particular role for ET-743 in the treatment of translocation-positive tumors. In addition, the modulation of EWS-FLI1 makes it a novel targeting agent for ESFT and suggests that further development of this compound for the treatment of ESFT is warranted.